2017
DOI: 10.1111/jam.13357
|View full text |Cite
|
Sign up to set email alerts
|

Exploring MALDI-TOF MS approach for a rapid identification ofMycobacterium aviumssp.paratuberculosisfield isolates

Abstract: The gold standard test for the diagnosis of paratuberculosis is still isolation of MAP by cultural methods, but additional assays, such as qPCR and subculturing for determination of mycobactin dependency are required to confirm its identification. We have provided here evidence pertaining to the usefulness of MALDI-TOF MS approach for a rapid identification of this mycobacterium among other members of M. avium complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Although the threshold recommended by the manufacturer enabled the correct identification of only 72.1% of the isolates, a lower cut-off for mycobacteria is commonly used (Alcolea-Medina et al, 2019;Buchan, Riebe, Timke, Kostrzewa, & Ledeboer, 2014;Mediavilla-Gradolph et al, 2015;Saleeb et al, 2011). In the authors' opinion, an important drawback of the MALDI-TOF MS technology in comparison with sequence analysis of housekeeping genes such as 16S rRNA, is that yet undescribed species will go undetected, either without any identification or as misidentifi- (Ravva, Harden, & Sarreal, 2017;Ricchi et al, 2017). The 25 M. avium isolates tested in the present study were all confirmed to be Mah by sequence analysis, and the first subspecies suggestion provided by MALDI-TOF MS was generally correct (80%).…”
Section: Identification Of Mycobacteria With Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…Although the threshold recommended by the manufacturer enabled the correct identification of only 72.1% of the isolates, a lower cut-off for mycobacteria is commonly used (Alcolea-Medina et al, 2019;Buchan, Riebe, Timke, Kostrzewa, & Ledeboer, 2014;Mediavilla-Gradolph et al, 2015;Saleeb et al, 2011). In the authors' opinion, an important drawback of the MALDI-TOF MS technology in comparison with sequence analysis of housekeeping genes such as 16S rRNA, is that yet undescribed species will go undetected, either without any identification or as misidentifi- (Ravva, Harden, & Sarreal, 2017;Ricchi et al, 2017). The 25 M. avium isolates tested in the present study were all confirmed to be Mah by sequence analysis, and the first subspecies suggestion provided by MALDI-TOF MS was generally correct (80%).…”
Section: Identification Of Mycobacteria With Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…other mycobacterial groupings that were not previously possible, including Mycobacterium kansasii (2), differentiating Mycobacterium chimaera from Mycobacterium intracellulare (3), and distinguishing Mycobacterium avium subsp. paratuberculosis from other M. avium subspecies (4). In this study, we set out to examine whether MALDI-TOF MS could be used as a typing tool for outbreak investigations.…”
mentioning
confidence: 99%
“…Ziehl-Neelsen stain-and PCR-positive colonies were then confirmed as MAP using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) [23]. Briefly, colonies were directly transferred to an MSP 384 target polished steel BC plate.…”
Section: Isolation and Identification Of Mapmentioning
confidence: 99%